Combined effects of electrical muscle stimulation and cycling exercise on cognitive performance - Ando, Soichi; Ishioka, Yuka; Kambayashi, Sari; Kano, Kosuke; Fujibayashi, Mami; Costello, Joseph T.; Sudo, Mizuki (Frontiers in Physiology, 2024)
The purpose of this study was to investigate whether a combination of electrical muscle stimulation (EMS) and cycling exercise is beneficial for improving cognitive performance. Eighteen participants (7 females & 11 males) performed a Go/No-Go task before and 2 min after i) cycling exercise (EX), ii) a combination of EMS and cycling (EMS+EX) and iii) a control (rest) intervention in a randomized controlled crossover design. In the EX intervention, the participants cycled an ergometer for 20 min with their heart rate maintained at ~120 beats·min-1. In the EMS+EX intervention, the participants cycled an ergometer simultaneously with EMS for 20 min, with heart rate maintained at ~120 beats·min-1. In the Control intervention, the participants remained at rest while seated on the ergometer. Cognitive performance was assessed by reaction time (RT) and accuracy. There was a significant interaction between intervention and time (p = 0.007). RT was reduced in the EX intervention (p = 0.054, matched rank biserial correlation coefficient = 0.520). In the EMS+EX intervention, RT was not altered (p = 0.243, Cohen’s d = 0.285) despite no differences in heart rate between the EX and EMS+EX interventions (p = 0.551). RT was increased in the Control intervention (p = 0.038, Cohen’s d = -0.529). These results indicate that combining EMS and cycling does not alter cognitive performance despite elevated heart rate, equivalent to a moderate intensity. The present findings suggest that brain activity during EMS with cycling exercise may be insufficient to improve cognitive performance when compared to exercise alone.